Sentience and conscious experience: Feeling dizzy on a virtual reality roller coaster ride - Pereira, Alfredo [UNESP] (My University, 2021)
Sentience is defined as the capacity for feeling that (according to the target paper in this journal issue) is biologically marked by the presence of ionic waves in neural tissue and the ‘lactate shuttle’ that provides fuel for the increase in wave amplitudes during wakefulness. Conscious experiences are proposed to be dynamic and relational phenomena, depending on the tuning of internal dispositions of sentience (the affective drive based on sentience that motivates conscious experiences) and affordances that arise in the domain of interaction of the agent with the physical and social environment. The expression of the capacity for feeling involves, besides sensations and emotions, two other types of mental function and respective neural correlates: cognitive and enactive. Focusing on the example of a virtual reality roller coaster (VRRC) conscious experience, I combine my first-person experience of feeling dizzy in a VRRC ride with thirdperson scientific experimental results about its neural correlates, involving the vestibular system and the direct perception of a visual cliff, to provide an explanation as to why some people feel dizzy during the downward phase of the ride, while others do not. The proposed explanation illustrates how affective, cognitive, and enactive functions are integrated in the formation of conscious episodes.
Keywords: Affective drive; Affordances; Dizziness; Interoception; Vestibular system; Virtual reality; Visual cliff